Case Report: Bilateral Deep Brain Stimulation Implantation on Different Targets for a Parkinson's Disease Patient With a Bullet in the Brain - Tian, Yu; Wang, Jiaming; Shi, Xin; Feng, Zhaohai; Jiang, Lei; Hao, Yujun (Frontiers in Human Neuroscience, 2022)
Patients requiring deep brain stimulation due to intracerebral metallic foreign substances have not been reported elsewhere in the world. Additionally, the long-term effects of metallic foreign bodies on deep brain stimulation (DBS) are unknown. A 79-year-old man with a 5-year history of Parkinson's disease (PD) reported that, 40 years ago, while playing with a pistol, a metallic bullet was accidentally discharged into the left brain through the edge of the left eye, causing no discomfort other than blurry vision in the left eye. DBS was performed due to the short duration of efficacy for oral medication. Because the bullet was on the left subthalamic nucleus (STN) electrode trajectory and the patient's right limb was primarily stiff, the patient received globus pallidus interna (GPi)-DBS implantation in the left hemisphere and STN-DBS implantation in the right hemisphere. During a 6-month postoperative follow-up, the patient's PD symptoms were effectively managed with no noticeable discomfort.